Multi-objective optimization of magnetorheological clutch with stationary housing - Duy, Bui Quoc; Thang, Le Duc; Tri, Diep Bao; Diep, Nguyen Ngoc; Hung, Nguyen Quoc (Vietnam Journal of Mechanics, 2022)
This study focuses on the development of magnetorheological fluid (MRF) based clutch systems for speed control of a rotary load. A new configuration for speed control of a rotary shaft using a magnetorheological clutch (MRC) with stationary winding housing and its mathematical model are proposed based on the Bingham plastic model of MRF. Multi-objective design optimization for MRCs simultaneously considering power consumption, transmitting torque, and rotating mass is then studied based on the derived mathematical model and electromagnetic finite element analysis (FEA) of the MRC. Subsequently, an optimal configuration of the proposed MRC is manufactured and experimentally investigated.